A New In Situ Microscopy Approach to Study the Degradation and Failure Mechanisms of Time‐Dependent Dielectric Breakdown: Set‐Up and Opportunities1. Issue 5 (17th April 2014) - Liao, Zhongquan; Gall, Martin; Yeap, Kong Boon; Sander, Christoph; Aubel, Oliver; Mühle, Uwe; Gluch, Jürgen; Niese, Sven; Standke, Yvonne; Rosenkranz, Rüdiger; Löffler, Markus; Vogel, Norman; et al.
<x xml:space="preserve">Abstract</x> The time dependent dielectric breakdown (TDDB) in copper/ultra‐low‐k on‐chip interconnect stacks of integrated circuits has become one of the most critical reliability concerns in recent years. In this paper, a novel experimental in situ microscopy approach using transmission X‐ray microscopy (TXM) and scanning transmission electron microscopy (STEM) is proposed to study TDDB degradation and failure mechanisms. It combines electrical testing and imaging techniques. Low‐dose bright field (BF) STEM inserting a small condenser aperture is chosen to reduce the beam damage of the dielectric material, while the electron spectroscopic imaging technique is used for the chemical analysis to detect the migration path of Cu atoms. This new experimental approach will contribute to an improved understanding of the TDDB effect.